Serum high concentrations of homocysteine and low levels of folic acid and vitamin B12 are significantly correlated with the categories of coronary artery diseases. Issue 1 (December 2017) - Ma, Yan; Peng, Duanliang; Liu, Chenggui; Huang, Chen; Luo, Jun
Abstract Background Homocysteine (Hcy) has been considered as an independent risk factor for coronary artery disease (CAD). Folic acid and vitamin B12 are two vital regulators in Hcy metabolic process. We evaluated the correlations between serum Hcy, folic acid and vitamin B12 with the categories of CAD. Methods Serum Hcy, folic acid and vitamin B12 from 292 CAD patients, including 73 acute myocardial infarction (AMI), 116 unstable angina pectoris (UAP), 103 stable angina pectoris (SAP), and 100 controls with chest pain patients were measured, and the data were analyzed by SPSS software. Results Compared to SAP patients, patients with AMI and UAP had higher Hcy levels with approximately average elevated (4-5) μmol/L, while SAP patients were approximately higher 8 μmol/L than controls. However, the levels of folic acid and vitamin B12 had opposite results, which in AMI group was the lowest, while in controls was the highest. CAD categories were positively correlated with Hcy (r = 0.286, p < 0.001), and negatively correlated with folic acid (r = -0.297, p < 0.001) and vitamin B12 (r = -0.208, p < 0.001). There were significant trend toward increase in the prevalence of high Hcy, low folic acid and vitamin B12 from controls, to SAP, to UAP, and to AMI. Conclusions The present study provide the valuable evidence that high concentrations of Hcy and low levels of folic acid and vitamin B12 are significantly correlated with CAD categories.